Preparation and chemical composition of the cell walls of Streptococcus mutans. - Cooper, H R (1975)
Purified cell walls from Streptococcus mutans strain BHT were prepared without the use of proteolytic enzymes in order to retain all cell wall constituents for chemical analysis. Of four methods employed, the Ribi cell fractionator produced disrupted cell suspensions which could be most thoroughly purified on sucrose gradients. Results of chemical analyses on purified cell walls prepared in this 8.9% glycerol teichoic acid, 33.6% non-peptidoglycan polysaccharide, and 49.9% peptidoglycan.